A Conflict Case Approach to Business Ethics - Brinkmann, Johannes (Journal of business ethics, 2004)
Departing from frequent use of moral conflict cases in business ethics teaching and research, the paper suggests an elaboration of a moral conflict approach within business ethics, both conceptually and philosophically. The conceptual elaboration borrows from social science conflict research terminology, while the philosophical elaboration presents casuistry as a kind of practical, inductive argumentation with a focus on paradigmatic examples.